Mecanismo de roteamento cross-layer em redes móveis Ad Hoc sem fio: um modelo de inteligência computacional com eficiência energética e suporte a mobilidade e QoE - CARVALHO, Tássio Costa de (Universidade Federal do Pará, 2017)
The evolution of wireless communications technologies has led to the need to provide network support for data and video applications and thus promote the development of new types of network configurations adapted to these new requirements. MANET is an important type of operation networks that employs mechanisms that can enable dynamic autoconfiguration, which requires a higher efficiency of its routing protocols. These protocols can also be challenged due to energy failures that are becoming increasingly severe in relation to the common networks failure; furthermore, the quality of the multimedia stream corresponds to a fundamental premise to the next generation wireless networks and the future Internet. This thesis proposes a new routing mechanism based on cross-layer paradigm to enhance the main routing protocols, by inserting new metrics in a computational intelligence decision making based on fuzzy systems, providing energy efficiency, support to manage mobility and quality experience to the devices, choosing the best route for the flow of computer networks. The proposal is evaluated in network simulator, demonstrating its efficiency through network results, quality of experience metrics and maximizing the communication’s lifetime.